Human capital development from islamic perspective - Hashi, Abdurezak Abdulahi; A, Bashiir (2009)
The term ‘human capital’ is being employed by economists, as labour (one of three factors of economic production), nonetheless, according to social psychologists, the term encompasses a wider scope of human capacity and ability of production and management of life. Besides this complementary divergence, both economists and social psychologists agree on the importance of human capital development to cope with the rapidly changing economic, political and administrative circumstances of human life. Today, the importance of improving the ‘human capital’ is best illustrated by the massive international and national efforts through educational and academic programs to enhance the administrative and productive talents of human individuals. Thus, academicians, social scientists and scholars of education have made an imperative endeavour, to expose effective measures of how to develop and improve revenues of the ‘human capital’. Likewise, through its educational system and intellectual teachings, Islam has provided certain ways and methods to develop and improve the human capacity of economic production and life management. This is because, according to the Qur’an, Allah (s.w.t) will not change the social, economic and political conditions of human communities unless communities give effort for change to the betterment of their economic and social life; nevertheless, such change for the betterment of economic and social life is not conceivable without effective human capital development. Through textual and analytical methods, this paper aims to expose conceptual understanding and theoretical measures as well as methods of human capital improvement in the Islamic perspective. The Qur’anic dictums and the Prophetic statements related to the subject would be exposed, while the opinions of the Muslim jurists and theologians on the subject would be unveiled.